PERBEDAAN FAKTOR EKSTERNAL DAN FAKTOR INTERNAL DALAM PERTIMBANGAN PEMBELIAN APARTEMEN DI SURABAYA ANTARA GENERASI X DAN GENERASI Y - Widya Sari Puspa Dewi Suyanto; Timoticin Kwanda; Njo Anastasia (Dimensi Utama Teknik Sipil, 2020)
The steady increase of human population and the limited living space encourages developers to make vertical residential namely apartments. The developers certainly need the right marketing strategy, one of them is determining the target age of the buyer. In this study, age is categorized into several generations, which is Gen X and Gen Y. Gen X and Gen Y have different characters and mindsets. This also makes a difference in consideration of buying an apartment. This research examines about the differences in the consideration of external factors and internal factors between Gen X and Gen Y in purchasing an apartment. External factors consist of physical condition of the apartment, location, environmental and financial factors. Meanwhile, internal factors consist of psychological, emotional, and intuition factors. The results stated that there were only differences in external environmental factors. Although there are no difference on other external and internal factors, Gen X tends to consider physical and location factors more, while Gen Y considers financial factors more. Meanwhile, all internal factors are considered more by Gen X than Gen Y.